2022
DOI: 10.1063/5.0090593
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities of thermocapillary flows in large Prandtl number liquid bridges between two coaxial disks with different radii

Abstract: We explore the geometric effects on the thermocapillary flow instabilities in large Prandtl number (Pr=1.4) liquid bridges between two coaxial disks with different radii under microgravity, focusing on the impacts of radius ratio Γr and aspect ratio Γ. The static deformation of the free surface is concerned by the solution of the Young-Laplace equation, and the linear stability analysis based on spectral element method is conducted for accurate identification of the instability characteristic. We observe that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Nayak et al 12 focused on the interfacial layer and shape effects of the nanoparticles of CNTs dispersed in water to explore the flow features of electromagnetic Darcy–Forchheimer flow. The study reported that "augmenting the interfacial layer parameter enhances heat transportation from the surfaces of the lower and upper disks.” Flow instabilities under microgravity for fluid flowing between co-axial disk was investigated by Wang et al 13 , Wang et al 14 . Vijay and Sharma 15 used FC-72-based nanofluid to examine the heat and mass transfer features of fluid flowing between co-axial rotating disks subjected to a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Nayak et al 12 focused on the interfacial layer and shape effects of the nanoparticles of CNTs dispersed in water to explore the flow features of electromagnetic Darcy–Forchheimer flow. The study reported that "augmenting the interfacial layer parameter enhances heat transportation from the surfaces of the lower and upper disks.” Flow instabilities under microgravity for fluid flowing between co-axial disk was investigated by Wang et al 13 , Wang et al 14 . Vijay and Sharma 15 used FC-72-based nanofluid to examine the heat and mass transfer features of fluid flowing between co-axial rotating disks subjected to a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…This motivated the development of more complicated numerical models including the static [23][24][25] and dynamic [26,27] interface deformations. Further complication of the model includes either unequal in radius [28,29] or non-flat supporting discs [30] as well as external thermal perturbations [31].…”
Section: Introductionmentioning
confidence: 99%